Autosomal dominant congenital Horner's syndrome in a Dutch family. - Hageman, G (1992)
A Dutch family is reported with congenital Horner's syndrome in five cases spanning five generations, with symptoms of varying degree but mainly ptosis and meiosis. Heterochromia iridium, anhidrosis, and enophthalmos were not present. The site of the lesion may be in the region between Gasser's ganglion and the short vertical segment of the internal carotid artery near the siphon. There are only four previous reports showing autosomal dominant inheritance of congenital Horner's syndrome.